2020
DOI: 10.1016/j.xpro.2020.100196
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the Bottom-Up Proteomic Analysis of Mouse Spleen

Abstract: Summary This protocol describes the comparative proteomic profiling of the spleen of wild type versus mdx-4cv mouse, a model of dystrophinopathy. We detail sample preparation for bottom-up proteomic mass spectrometry experiments, including homogenization of tissue, protein concentration measurements, protein digestion, and removal of interfering chemicals. We then describe the steps for mass spectrometric analysis and bioinformatic evaluation. For complete details o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…FABP3 had a higher association with muscle weakness in polymyositis and dermatomyositis patients than CK and myoglobin serum levels (Zhang et al, 2016). A recent study showed that serum levels of FABP3 might represent a novel biomarker for Duchenne muscular dystrophy (Dowling et al, 2020). To the best of our knowledge, this is the first report that shows an increased abundance of FABP3 in human urine after strenuous exercise and its correlation with serum biomarkers of muscle damage.…”
Section: Discussionmentioning
confidence: 65%
“…FABP3 had a higher association with muscle weakness in polymyositis and dermatomyositis patients than CK and myoglobin serum levels (Zhang et al, 2016). A recent study showed that serum levels of FABP3 might represent a novel biomarker for Duchenne muscular dystrophy (Dowling et al, 2020). To the best of our knowledge, this is the first report that shows an increased abundance of FABP3 in human urine after strenuous exercise and its correlation with serum biomarkers of muscle damage.…”
Section: Discussionmentioning
confidence: 65%
“…Verification analyses were carried out with samples derived from a minimum of 4 wild type and 4 dystrophic mice. Comparative tissue proteomics was carried out by standardized procedures, as previously described in detail [ 40 , 41 ]. Mice were sacrificed in the Bioresource Unit of the University of Bonn and muscle specimens were quick-frozen in liquid nitrogen and then transported on dry ice to Maynooth University [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The label-free liquid chromatography mass spectrometric analysis of EOMs from wild type versus mdx-4cv mice was carried out using a Thermo Orbitrap Fusion Tribrid mass spectrometer (Thermo Fisher Scientific, Waltham, MA, USA). Details of the proteomic workflow describing all preparative steps and analytical procedures using data-dependent acquisition, as well as bioinformatic data handling, were recently outlined in detail [ 41 ]. A Thermo UltiMate 3000 nano system was used for reverse-phased capillary high-pressure liquid chromatography and directly coupled in-line with the Thermo Orbitrap Fusion Tribrid mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For bottom-up proteomics, a variety of sample preparation approaches have been developed for optimum protein extraction [150][151][152], including the widely employed filteraided sample preparation (FASP) method that can be used to exchange buffers and remove incompatible detergents prior to MS-based analysis [153]. The routine bottom-up proteomic analysis pipeline can be divided into a series of consecutive steps [152] comprising (i) sample harvesting from complex cellular mixtures, (ii) sample pre-treatment, such as enrichment procedures using differential centrifugation or affinity isolation of protein constellations, or depletion procedures to enrich low-abundance proteins, (iii) initial sample protection from excess proteolysis using suitable protease inhibitor cocktails, (iv) efficient homogenization using mechanical grinding approaches or sample pulverization with liquid nitrogen, (v) protein extraction via precipitation or other biochemical methods, (vi) protein quantification using sensitive dye binding or other reliable assay systems, (vii) chemical reduction and alkylation of protein samples, (viii) protein digestion using enzymes such as trypsin for the generation of distinct peptide populations, (ix) peptide fractionation and MS analysis, (x) protein identification, and (xi) systems bioinformatic analysis of identified proteoforms and their PTMs [154][155][156]. Figure 2 compares the main differences in the preparation of protein samples between top-down proteomics and bottom-up proteomics, i.e., the isolation of intact proteoforms versus the enrichment of protein fractions.…”
Section: Sample Preparation Protein Digestion and Bottom-up Proteomicsmentioning
confidence: 99%